Investigating the impact of coach behaviours and coach-athlete relationships on psychological safety - Senel, E.; Jowett, S.; Adilogullari, I.; Kerr-Cumbo, R. (International Journal of Sport and Exercise Psychology, 2025)
The aims of the present study were two-fold: (a) to examine the links between two sets of perceived coach behaviours (supportive and controlling) and psychological safety, as well as (b) to explore whether the quality of the coach-athlete relationship explains the link between the two sets of coach behaviours and psychological safety. A total of 295 Turkish athletes (42% female and 58% male) in team sports with a mean age of 21.69 (±4.71) completed a multi-section questionnaire that measured the three main variables of the study, namely, coach behaviours, coach-athlete relationship quality, and psychological safety. Structural equation modelling revealed that both perceived coach behaviours (supportive and thwarting/controlling) and coach-athlete relationship quality predicted athletes` psychological safety in their team. Moreover, the quality of the coach-athlete relationship explained the association between athletes` perceptions of coach behaviours and psychological safety within the team context. The findings of this study contribute to growing research that examines the processes by which psychological safety can be nurtured in sports. While evidence thus far suggests that a coach orchestrates the environment, the findings of this study would seem to suggest that athletes, through good-quality relationships with their coaches, can stimulate the creation of a psychologically safe environment. The findings are discussed with a particular emphasis on future research directions and practical applications.